2023
DOI: 10.3389/fimmu.2023.1105973
|View full text |Cite
|
Sign up to set email alerts
|

PHLDA1 modulates microglial response and NLRP3 inflammasome signaling following experimental subarachnoid hemorrhage

Abstract: Balancing microglia M1/M2 polarization is an effective therapeutic strategy for neuroinflammation after subarachnoid hemorrhage (SAH). Pleckstrin homology-like domain family A member 1 (PHLDA1) has been demonstrated to play a crucial role in immune response. However, the function roles of PHLDA1 in neuroinflammation and microglial polarization after SAH remain unclear. In this study, SAH mouse models were assigned to treat with scramble or PHLDA1 small interfering RNAs (siRNAs). We observed that PHLDA1 was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Upregulation of phosphorylated TAK1 promotes NF-κB p65 nuclear translocation and NLRP3 upregulation, inducing neuronal pyroptosis [64]. Additionally, LDC7559, a novel GSDMD inhibitor, inhibited neuronal pyroptosis post-SAH [65]. However, several studies have reported mechanisms underlying NLRP3-mediated microglial pyroptosis in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of phosphorylated TAK1 promotes NF-κB p65 nuclear translocation and NLRP3 upregulation, inducing neuronal pyroptosis [64]. Additionally, LDC7559, a novel GSDMD inhibitor, inhibited neuronal pyroptosis post-SAH [65]. However, several studies have reported mechanisms underlying NLRP3-mediated microglial pyroptosis in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 and caspase inhibitors have been explored for the treatment of neurodegenerative diseases by targeting overactivated pyroptosis and have shown certain effects (44,118,119). Recently, LDC7559, a newly developed selective GSDMD inhibitor, was reported to promote brain functional recovery by inhibiting over-activated pyroptosis by directly blocking the GSDMD-N-terminus (120,121). However, whether these inhibitors may also be used for cancer treatment remains to be investigated.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Unfortunately, this study did not deeply explore the bidirectional regulation and causal relationship between intestinal microflora, NLRP3 inflammasome and cerebral hemorrhage after ICH. In addition, silymarin, atorvastatin, baicalein, mst4, h2s, a68930induced activation of drd1, fimasartan, p2y6 receptor activation, histone deacetylation 10, verbascoside, verapamil, cordycepin, dexmedetomidine, andrographolide and others can directly or indirectly inhibit NLRP3 activation to reduce nerve inflammation, improve secondary brain injury after ICH, and play a neuroprotective role [83][84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…INT-777, a TGR5 agonist, can inhibit the NLRP3 activation through TGR5/cAMP/ PKA signaling pathway, alleviate acute cerebral edema and neuroinflammation, and hippocampal neuronal degeneration 28 days after SAH [89]. Inhibition of NLRP3 activation by PHLDA1 can induce M2 polarization of microglia after SAH and improve neuroinflammation and neuronal apoptosis [90]. Takinib can reduce oxidative damage, neuroinflammation, brain edema and neuronal apoptosis after SAH by inhibiting TAK1-ROS-NLRP3 signaling pathway, and improve neurological deficit [91].…”
Section: Hemorrhagic Strokementioning
confidence: 99%